Some effects of our time for formation teacher of Special Education - Leandra Boer Possa; Maria Inês Naujorks (Universidade Federal de Santa Maria (UFSM), 2014)
The desire to know and problematize what seems naturalized around the training of Special Education teachers are the effects of a neoliberal political strategy that operates in the processes of objectification/subjection of a person who is produced as a Special Education teacher. The plot wich legitimizes processes of formation, as an eternal moment of learning for the profession, is a mode of subjectivation in which we are all captured on ourselves to perform a kind of power that bends from the relations we put on ourselves and on the others. This research problematizes the discussions around the Special Education teachers' formatio from three themes, they are: Inclusion, Inclusive school and Inclusive education for all, the duo of Special Education that presents the clinical field in opposite direction of the Education; and all-encompassing and comprehensive perspective that is bypassing the political discourse of teacher training in Special Education. To conclude, we point out the need to naturalize as a model for teacher training in Special Education, so that we can realize contingently regimes of truth and political rationality that organize and structure such training. We propose to think about the effects that these regimes of truth, since we can not escape them, produce in the way they subjectivate those, who by training, teachers are up in such a field.